Silica Gel/Thionyl Chloride: An Efficient Reagent for theConversion of Alcohols to Symmetrical Dialkyl Sulfites - Kazemi, Foad; Reza Kiasat, Ali; Fadavipoor, Elham (Asian Journal of Chemistry, 2010)
Silica gel/thionyl chloride is used as an efficient reagent for symmetrical dialkyl sulfite preparations from their corresponding alcohols under mild reaction conditions. The isolated yields are good to excellent and sterically hindered alcohols have been successfully converted to dialkyl sulfites.